2016
DOI: 10.5229/jecst.2016.7.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Scanning Electrochemical Microscopy (SECM) Coupled to Atomic Force Microscopy with Sub-Micrometer Spatial Resolution to the Development and Discovery of Electrocatalysts

Abstract: Development and discovery of efficient, cost-effective, and robust electrocatalysts are imperative for practical and widespread implementation of water electrolysis and fuel cell techniques in the anticipated hydrogen economy. The electrochemical reactions involved in water electrolysis, i.e., hydrogen and oxygen evolution reactions, are complex inner-sphere reactions with slow multi-electron transfer kinetics. To develop active electrocatalysts for water electrolysis, the physicochemical properties of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…One of the recent developments is to couple AFM with SECM to obtain localized topography and electrochemical activity information . Zampardi et al have previously demonstrated a AFM/SECM combined investigation of SEI at a glassy carbon surface .…”
Section: Advanced Electrochemical Scanning Probe Microscopymentioning
confidence: 99%
“…One of the recent developments is to couple AFM with SECM to obtain localized topography and electrochemical activity information . Zampardi et al have previously demonstrated a AFM/SECM combined investigation of SEI at a glassy carbon surface .…”
Section: Advanced Electrochemical Scanning Probe Microscopymentioning
confidence: 99%